Pendekatan Tajdid Umar Abdul Aziz Melalui Institusi al-Mazalim Dalam Menangani Isu Kezaliman Dan Penyelewengan: The Approach of Tajdid’s Umar Abdul Aziz Through the Institution of al-Mazalim in Dealing with the issues of Deviation and Misappropriation - Hamidi Abdul Ghani; Abdul Azib Hussain; Nurul Akma Mohamed (RABBANICA - Journal of Revealed Knowledge, 2023)
The behaviors of deviation, misappropriation, and abuse of power are in direct opposition to the principles and teachings of Islam. Islam strictly prohibits the violation of justice and the betrayal of trust. Nevertheless, instances of deviation, misuse, and abuse of authority by governmental authorities persist. Consequently, the establishment of the al-Mazalim Institution occurred, with its primary objective being to eradicate the vicious actions perpetrated by government officials in power. In the annals of Islamic history, Caliph Umar bin Abdul Aziz Rah. stands out as a renowned figure who successfully eliminated the misconduct exhibited by government officials and reinstated the rights of the populace that had been unlawfully seized. This article aims to provide an overview of Umar bin Abdul Aziz Rah’s Tajdid strategy through the al-Mazalim Institution. It will explore how this technique was utilized to enforce justice and prevent individuals from deviating from the government. This research employs a qualitative approach, explicitly using a bibliographic methodology combined with a descriptive content analysis technique. The research data was acquired from scholarly publications and academic books, with a particular emphasis on works about the biographical account of Umar bin Abdul Aziz. The study outcomes demonstrate that Umar bin Abdul Aziz effectively implemented eleven tajdid measures to promote justice and combat governmental corruption among officials. The tajdid method of Umar bin Abdul Aziz should be reproduced by individuals in positions of authority to attain divine favor and promote the nation’s welfare. Kezaliman, penyelewengan dan penyalahgunaan kuasa adalah tindakan yang bertentangan dengan ajaran Islam yang menyuruh menegakkan keadilan dan menunaikan amanah. Namun kezaliman, penyelewengan dan penyalahgunaan kuasa oleh pemerintah masih berlaku. Justeru , diwujudkan Institusi al-Mazalim yang berperanan menghapuskan kemungkaran yang dilakukan oleh pegawai-pegawai kerajaan yang memerintah. Sepanjang sejarah Islam, khalifah Umar bin Abdul Aziz Rah. merupakan khalifah yang paling terkenal membanteras kezaliman yang dilakukan oleh pegawai kerajaan dan mengembalikan semula hak rakyat yang dirampas. Artikel ini akan menghuraikan pendekatan tajdid Umar bin Abdul Aziz Rah. melalui Instutusi al-Mazalim dalam menegakkan keadilan dan menghindari rakyat dari kezaliman pemerintah. Kajian ini berbentuk kualitatif jenis kepustakaan dengan gaya analisis kandungan secara deskriptif. Data-data kajian diperolehi dari artikel dan buku terutamanya buku yang berkaitan sejarah hidup Umar bin Abdul Aziz. Artikel menyimpulkan bahawa Umar bin Abdul Aziz telah berjaya menegakkan keadilan dan menghapuskan penyelewengan pegawai kerajaan dengan menggunakan sepuluh pendekatan tajdidnya. Lantaran itu, pendekatan tajdid Umar bin Abdul Aziz boleh dijadikan sebagai model yang wajar dicontohi oleh pihak yang berkuasa untuk mendapat keredhaan Allah dan kemakmuran negara.